Perlindungan Rahasia Medis Pasien dalam Penerapan Rekam Medis Elektronik di Klinik Citra Medika Medan Marelan - Mohd Taufiq Kamil Husaini; Irsyam Risdawati; Aditya Nafidz Farhan; Ahmad Yasin; Fadhlul Akhyar Zi; Gina Zalfa Salsabila S; Muhammad Mas’ud Herlambang (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The implementation of Electronic Medical Records (EMR) represents a crucial aspect of healthcare digital transformation aimed at enhancing the effectiveness, efficiency, and quality of medical services. However, this digitalization also raises significant concerns regarding the protection of patients’ medical confidentiality, which constitutes a fundamental privacy right safeguarded by law. This study aims to analyze the legal framework governing the protection of patients’ medical confidentiality in EMR implementation, examine its practical application at Citra Medika Clinic in Medan Marelan, and identify existing obstacles as well as efforts to address them. This research employs an empirical juridical approach with a descriptive-analytical method. Primary data were obtained through an interview with Mrs. Mifta Ariani Hasibuan, Am.Keb., serving as the PRB and Prolanis administrative officer at the clinic, while secondary data were collected through literature review, including laws, legal doctrines, and relevant scientific journals. Data were analyzed qualitatively using the Miles and Huberman Interactive Analysis Model, and validity was ensured through triangulation techniques. The findings reveal that the clinic has implemented confidentiality protection measures through restricted access, user authentication systems, and data security protocols in accordance with applicable regulations. Nevertheless, several challenges persist, including suboptimal access control, limited user awareness, and the need for continuous monitoring of EMR usage. Therefore, strengthening governance systems, improving user compliance, and conducting regular evaluations are essential to ensure optimal legal protection of patients’ medical confidentiality in digital healthcare services and sustainable healthcare system development.